Magnetic resonance imaging to estimate tissue deformations during penile clamp application: A case series. (November 2020) - Lemmens, Joe; Peko Cohen, Lea; Worsley, Peter R; Everitt, Chris; Broadbridge, Jackie; Gefen, Amit; Rees, Rowland W; Drake, Marcus; Macaulay, Margaret C; Fader, Mandy; Bader, Dan L
Background: Penile clamps provide a means of preventing urinary incontinence in males following radical prostatectomy. In order for the devices to function, significant mechanical loads need to be applied to the penile tissues to close the urethra. However, such loads have the potential to cause damage to the vulnerable skin and underlying soft tissues. Accordingly, the study aimed to estimate the magnitudes of tissue deformations resulting from penile clamp application in three individual cases. Methods: Three individuals were recruited who currently use penile clamps to manage urinary incontinence following radical prostatectomy. Magnetic resonance images (MRI) of the penis were taken to produce a series of high contrast coronal and sagittal images both before and during the application of two commercially available clamps, modified for MRI compatibility. Tissue thickness measurements were estimated with the clamps in-situ and normalised to the unloaded baseline state. Results: The estimated magnitude of tissue deformations resulting from clamp application ranged between 68% and 84%. There were minimal differences in these deformations between the clamp designs, both of which appeared effective in closing the urethra. Local stress concentrations were observed in the tissues, which were deformed around the shape of the clamp. Conclusions: MRI enabled quantification of local tissue deformation during penile clamp application. The results revealed that clamps created large tissue deformations in all three cases, regardless of design. This information could inform the development of new clamp designs and materials to minimise the potential for tissue damage. Level of evidence: 4